The Role of Tuha Peut in Optimizing the Nutrition of Pregnant Women and Monitoring Related to the Implementation of the Qanun in Macah Village, Suka Makmue District, Nagan Raya Regency - Zuhra, Fatimah; Teungku Nih Farisni (Jurnal EduHealth, 2022)
Background Pregnancy is a process that begins with conception and continues through the fetus's birth.Poor maternal nutritional status is associated with adverse birth outcomes, and nutrition plays a major and important role in the health of both the mother and the child.However, the connection that exists between maternal nutrition and the outcomes of birth can serve as the foundation for the development of nutrition interventions that will decrease mortality, morbidity, and the cost of health care while also enhancing birth outcomes and long-term quality of life.application of the qanun in Macah Village, District of Suka Makmue, Nagan Raya Regency.This exploration technique utilizes expressive subjective examination, which is a strategy used to answer research issues connected with information as stories starting from meetings, perceptions, and exhuming of reports coming about because of the job of tuha peut in enhancing the nourishment of pregnant ladies and checking connected with the execution of qanuns in Macah Town, Suka Makmue Locale, Nagan Raya Regime, which is very great thinking about that the program is done regularly and improvement has been completed in a reasonable way consistently.The conclusion is that the implementation of qanuns in Macah Village, Suka Makmue District, Nagan Raya Regency, which has been going well and is in accordance with the technical guidelines for preventing KEK in pregnant women, namely Qanun Gampong Macah Village, Suka Makmue District, Nagan Raya Regency, plays a role in optimizing the nutrition of pregnant women.